Cross-sectional characterization techniques as the basis for knowledge-based design of graded CVD TiN-TiB2 coatings. (February 2018) - Tkadletz, Michael; Schalk, Nina; Mitterer, Christian; Keckes, Jozef; Pohler, Markus; Czettl, Christoph
Abstract: Chemical vapor deposited h-TiB2 coatings exhibit a high hardness (up to ~ 45 GPa) and outstanding wear resistance; they are thus frequently used for machining of Ti alloys and refractory metals. The coating architecture of a fcc-TiN base-layer followed by the h-TiB2 top-layer results in a sharp transition of microstructure, residual stress, hardness and Young's modulus and consequently in a weak interface. In order to strengthen the interface, a ~ 6.5 μm thick Ti(N, B) coating consisting of 6 individual sublayers with gradually increasing boron content from pure fcc-TiN, via 5, 15, 30 and 45 at.% B, to pure h-TiB2 was synthesized within this work. Subsequently, cross-sectional characterization techniques were applied to investigate the influence of the boron addition across the film thickness. The elemental and microstructural evolution was studied using scanning and transmission electron microscopy, which revealed a significantly decreasing grain size with increasing B content. Synchrotron X-ray nanodiffraction was performed to determine the phase and residual stress evolution of the sample. The rising B content caused a gain in h-TiB2 phase fraction, which strongly affects the residual stress provoking a change from ~ 1 GPa tensile to ~ 1 GPa compressive across the coating thickness. Nanoindentation measurements utilizing continuous stiffness and modulus mapping techniques revealed a strong correlation of cross-sectional nanohardness with phase composition, showing an almost linear increase from 23 GPa for fcc-TiN to 43 GPa for h-TiB2 . An exception was found for the sublayer with 45 at.% B, which revealed a disordered sub-stoichiometric h-TiB2 − x Nx structure with a strong gradient in residual stress and a low hardness and Young's modulus of 28 GPa and 400 GPa, respectively. The obtained results provided the basis for the development of an improved interface architecture, demonstrating the potential of advanced characterization methods for a knowledge-based coating design. Highlights: Cross-sectional characterization of chemical and microstructural properties on the nanometer scale Continuous reduction of grain size of TiN coating by gradual increasing B content Gradual transition from fcc-TiN to h-TiB2 by gradual B addition Significant influence of B content on mechanical properties of TiBN coatings Advanced characterization techniques as tools for a knowledge based coatings design